1,4-Disubstituted aromatic piperazines with high 5-HT2A/D2 selectivity: quantitative structure selectivity investigations, docking, synthesis and biological evaluation - Möller, Dorothee; Mohamed, Ismail Awadalla Salama; Kling, Ralf; Hübner, Harald; Gmeiner, Peter (Bioorganic & Medicinal Chemistry, 2015)
UnivIS-Import:2015-10-26:Pub.2015.nat.dchph.lphch.14disu

Synthesis and binding profile of haloperidol-based bivalent ligands targeting dopamine D2-like receptors - Mohamed, Ismail Awadalla Salama; Löber, Stefan; Hübner, Harald; Gmeiner, Peter (Bioorganic & Medicinal Chemistry Letters, 2014)
Homodimers of dopamine D2-like receptors are suggested to be of particular importance in the pathophysiology of schizophrenia and, thus, serve as promising targets for the discovery of atypical antipsychotics. This study describes the development of a series of novel bivalent molecules with a pharmacophore derived from the dopamine receptor antagonist haloperidol. These dimers were investigated in comparison to their monomeric analogues for their D2long, D2short, D3, and D4 receptor binding and the ability to bridge two neighboring receptor protomers. Radioligand binding studies provided diagnostic insights when Hill slopes close to two for the bivalent ligand 13 incorporating 22 spacer atoms and a comparative analysis with monovalent control ligands indicated a bivalent binding mode with a simultaneous occupancy of two neighboring binding sites. © 2014 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2014.nat.dchph.lphch.synthe
Keywords: Binding affinity; Bivalent ligands; Dopamine; GPCR dimers